2019
DOI: 10.1007/s11145-019-09944-9
|View full text |Cite
|
Sign up to set email alerts
|

Literacy skills and online research and comprehension: struggling readers face difficulties online

Abstract: The present study evaluated the extent to which literacy skills (reading fluency, written spelling, and reading comprehension), together with nonverbal reasoning, prior knowledge, and gender, are related to students' online research and comprehension (ORC) performance. The ORC skills of 426 sixth graders were measured using a Finnish adaptation of the Online Research and Comprehension Assessment. Results of a structural equation model showed that these ORC skills were divided into six highly correlated factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
3
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 65 publications
6
38
3
2
Order By: Relevance
“…Specifically, performance on Version 1 is explained by general non-verbal reasoning, prior knowledge on the topics, offline text reading comprehension, attention (especially concentration) and memory skills. This is totally consistent with what reported in published studies about the predictors and components of online reading skills (Cromley et al, 2010; Tarchi, 2010; Snowling, 2013; Kanniainen et al, 2019). A different explanation is probably necessary for the results of the regression analysis for Version 2, where linguistic difficulty seems to have been central to performance, and may also have biased the reliability and internal consistency of the results.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Specifically, performance on Version 1 is explained by general non-verbal reasoning, prior knowledge on the topics, offline text reading comprehension, attention (especially concentration) and memory skills. This is totally consistent with what reported in published studies about the predictors and components of online reading skills (Cromley et al, 2010; Tarchi, 2010; Snowling, 2013; Kanniainen et al, 2019). A different explanation is probably necessary for the results of the regression analysis for Version 2, where linguistic difficulty seems to have been central to performance, and may also have biased the reliability and internal consistency of the results.…”
Section: Discussionsupporting
confidence: 92%
“…A final interesting issue in literacy research is gender-related differences. Several studies showed an advantage for girls in reading fluency and reading comprehension (Logan and Johnston, 2009, 2010; Torppa et al, 2018) and similar patterns have also been observed in other studies on Online Reading Comprehension (Forzani, 2016; Salmerón et al, 2018; Kanniainen et al, 2019). McKenna et al (2012) reported that middle school girls have more positive reading attitudes toward reading print texts for recreational as well as academic purposes, while their attitudes toward reading digital texts are better for academic purposes, but not for recreational purposes.…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations